The effect of organisational structure and managerial practices on the clinical behaviour and job satisfaction of primary health care doctors, as knowledge workers, in the managed health care industry in South Africa - Pillay, Rubin (School of Management Studies, 2014)
Bibliography: leaves 196-223.